Complex Disasters
XXVII, 394 p. 27 illus., 21 illus. in color.
Keywords: This is an important, timely and provocative book! The authors explore the contested terrain of risk and disaster, challenging the reader through diverse, and at times disruptive, perspectives and analysis. Unusually for material on this subject, I found the book very accessible. It deserves to be widely read and I expect it to have significant influence on thinking and policy. The volume is also a wonderful tribute to Professor Helen James. -- Emeritus Professor John Handmer, FASSA, Senior Research Scholar, International Institute for Applied Systems Analysis (IIASA), Vienna Exploration of the complexity of disasters in a multi-hazard context is crucial to improving future disaster resilience. For policymakers the book provides evidence of the need to invest in disaster resilience and adaptation to address the growing threats posed by complex disasters. — Andrew Gissing, Fellow at Macquarie University and General Manager, Risk Frontiers, Sydney, Australia The authoring of complex disasters: compounding, cascading, and protracted is both timely and essential. This book makes a significant contribution in helping policy makers, academics, strategists, operational leaders as well as anyone else who is concerned about the current and future challenges in disaster risk management to think differently about disasters. -- Mark Crosweller AFMS, former Director-General Emergency Management, Canberra, Australia This Edited book introduces the concept of complex disasters and considers both disaster risks and impacts across the disaster management spectrum – Prevention – Preparation – Response and Recovery. Three types of complex disasters are analysed – ‘compound’, ‘cascading’ and ‘protracted’. The book will be useful to researchers in climate, disaster, or environmental and economic policy, disaster risk reduction, and climate change studies, and practitioners and policy makers applying disaster theory and knowledge into policy and decision-making. Anna Lukasiewicz researches topics around the distribution of natural resources; water governance; disaster justice and natural hazard management. She works at the interface of justice and natural resource management. Tayanah O’Donnell is an Honorary Associate Professor at the Australian National University and Partner with Deloitte, climate and sustainability. Her research interests include: climate and environmental regulation and policy, managed retreat, disaster resilience and climate change adaptation. She was previously a senior executive at the Australian Academy of Science.